RESPONSIBILITIES OF NOTARIES IN MAKING AUTHENTIC DEEDS BASED ON LAW NUMBER 2 OF 2014 AND THE NOTARY CODE OF ETHICS - Dwi Kurniawan, Irfan; Edison Purba, John; Wira Utama, H. M. (LPPM, Universitas Muhammadiyah Riau, 2026)
Notaries have a strategic position as a public official who is authorized by law to make authentic deeds. Deeds made by notaries have perfect evidentiary power and are the main evidence in every legal transaction. Therefore, the legal responsibility of notaries in the process of making authentic deeds is a very important aspect to be studied. This research aims to find out the Responsibilities of Notaries in the Making of Authentic Deeds Based on Law No. 2 of 2014 and the Notarial Code of Ethics and to find out the Formation of Authentic Deeds by the Notary Profession Based on Law No. 2 of 2014 and the Notary Code of Ethics. The method used in this study is normative juridical, with a legal approach and a study of related documents. The results of the study show that notaries can be asked to hold legal answers both civilly, criminally, or administratively, if it is proven that they have committed violations or negligence in carrying out their duties, including in the case of including data that is not in accordance with the circumstances of the case. In addition, the Notary Code of Ethics also provides a binding moral and professional foundation for notaries in carrying out their duties. The conclusion of this study emphasizes that the role and responsibility of legal must be carried out with integrity, prudence, and adhering to the certainty of positive law and professional ethics, in order to maintain public trust and ensure legal certainty in society